Distribution analysis of coral reefs for development of marine tourism in Weh Island, Aceh, Indonesia - Tumiar Sidauruk; M Taufik Rahmadi; Sugiharto Sugiharto; Ayu Suciani; Rima Meilita Sari; Eni Yuniastuti (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2022)
One of the most attractive ecosystems to be used as tourist destinations is coral reefs. The coral reef ecosystem on Weh Island, Aceh, Indonesia is one of the coastal ecosystems that have a strategic role in ecological and economic development. One of the ecological and economic development efforts can be done through marine tourism. This study aims to analyze the distribution of coral reefs to develop marine tourism in Weh Island. This study uses Landsat 8 OLI image data and field observations. The technique used in this research is the image data analysis technique using multispectral classification. The results showed that the coral reefs on Weh Island in 2020 amounted to 13,136,000 Ha. Therefore, the development of marine tourism must create tourism zones to maintain the sustainability of coral reef ecosystems.